China During the Great Depression : Market, State, and the World Economy, 1929-1937 - Shiroyama, Tomoko, 1965- (Book collections on Project MUSE., 2009)
The aim of this book is not merely to show that China could not escape the consequences of the Great Depression - in her case it led to a slump and forced her to adopt a new monetary system - but also to offer a new perspective for understanding Chinese history.